Assessment of awareness on consumption of irradiated foods among Saudi population using a validated psychometric scale - Shubayr, Nasser (Frontiers in Public Health, 2024)
Despite the application of food irradiation for enhancing food safety, many consumers lack an understanding of its fundamental principles, often misinterpreting the information and exhibiting negative perceptions towards foods treated with ionizing radiation. This study focuses on evaluating public awareness regarding the consumption of irradiated food within Saudi Arabia, utilizing the Awareness Scale on Consumption of Irradiated Foods (ASCIF), a developed and validated tool. The ASCIF encompasses four constructs: concepts, awareness, labeling, and safety concerning irradiated foods. The average scores for each subscale and the aggregate ASCIF score were determined, with the analysis incorporating both descriptive and inferential statistical methods. The study's sample of 712 individuals predominantly consisted of females (53.37%), individuals aged 18-30 years (55.62%), those holding a bachelor's degree or higher (70.79%), participants earning less than SAR 5000 (42.70%), students (37.08%), and singles (66.85%). The overall mean scores for each category were as follows: safety (2.87 ± 0.92), concept (3.18 ± 0.79), label (3.44 ± 1.15), and awareness (2.68 ± 1.03). The overall mean score for the ASCIF was 3.02 ± 0.81, a diverse spectrum of awareness, with the majority of participants (62.92%) exhibiting intermediate awareness, while 17.98% displayed poor awareness, and 19.10% demonstrated high awareness. Logistic regression analysis identified age and educational attainment as significant predictors of awareness levels (p < .001). These results highlight a moderate understanding of irradiated foods among the Saudi population, with significant variations based on demographic factors. The study's conclusion emphasizes the necessity for tailored educational initiatives that cater to specific demographic groups to enhance understanding and awareness of irradiated food technologies in Saudi Arabia. This study thereby provides valuable insights for policymakers and health educators in designing effective communication strategies about irradiated foods.